Do ladies with a high BMI achieve a normal birth. (18th April 2012) - Ballal, S; Finney, V; Ramachandran, N; McCormack, J
Abstract : Introduction: In 2008 CEMACH conducted a three year obesity in pregnancy project. They found that only 55% of women with a BMI ≥35 had a spontaneous vaginal delivery, with 46% of women with a BMI ≥50 delivering by caesarean sections. Methods: The aim of our audit was to assess the outcome of delivery in those women with a booking BMI of 45 or more between 2008-2010 and any complications associated with their delivery. This was a pilot study and data collection is still ongoing. 37 patients were included on that period (11 primips, 26 multips). Results: 16 patients (43%) had their labour induced and 7 (17.9%) were delivered by elective C/S. 35% of these women had a BMI over 50 and only 4 had a natural birth and they were all multigravid. Only 4 out of 11 primip compared to 19 out of 26 multiparous women in total achieved a vaginal birth, and 45% primips had C/S. 8 patients developed complications including major PPH and wound infections. Conclusion: We are aware of the high complication rate associated with high BMI and pregnancy, especially out of hours. We have to be cautious drawing conclusions from our data due to the small numbers but as nearly half our primigravid ladies had caesarean sections, should we book all ladies with a BMI over 45 for an elective caesarean in accordance with our and CEMACH finding?